THE EFFECT OF MINERAL FERTILIZATION ON ACHENES YIELD AND FUNGAL COMMUNITIES ISOLATED FROM THE STEMS OF MILK THISTLE Silybum marianum (L.) GAERTNER - Bożena Cwalina-Ambroziak; Jadwiga Wierzbowska; Marta Damszel; Teresa Bowszys (Acta Scientiarum Polonorum: Hortorum Cultus, 2012)
The achenes of milk thistle contain a variety of lipids, proteins and biologically active substance, which is why they are used in pharmaceutical and cosmetic products, as well as an ingredient of functional food and animal feed. The yield of milk thistle is determined by both agrotechnological factors (sowing date, cultivation regime, fertilization) and the health status of plants. The study was conducted over the years 2009–2011 in experimental plots located in Tomaszkowo (NE Poland). The experiment involved the following treatments: 1. N0PK, 2. N0PKMg, 3. N0PKMg+microelement B, 4. N1PK, 5. N1PKMg, 6. N1PKMg+B, 7. N2PK, 8. N2PKMg, 9. N2PKMg+B, 10. N3PK, 11. N3PKMg, 12. N3PKMg+B (where: N0 – without nitrogen fertilization, N1 – 40 kg · ha-1 /ammonium nitrate/, N2 – 80 kg · ha-1, N3 – 120 kg · ha-1, P – 40 kg · ha-1 /triple superphosphate/, K – 117 kg · ha-1 /60% potash salt/, Mg – 20 kg · ha-1 /kieserite/ before sowing, B – foliar application/Bormax/). The structure of fungal communities colonizing the stems of milk thistle was analyzed at the laboratory. Achene yield was determined after harvest. The composition of fungal communities colonizing the stems of milk thistle was affected by weather conditions, and macronutrient and B fertilization. Potential pathogens had a 50–80% share of the fungal community. The predominant species was Alternaria alternata, fungi of the genus Fusarium were identified less frequently (six species), while Rhizoctonia solani, Botrytis cinerea and Phoma spp. were encountered only sporadically. The abundance of A. alternata was lower in treatments without N fertilization and with N fertilization at 40 kg P · ha-1. In contrast to A. alternata, fungi of the genus Fusarium were less abundant in treatments with Mg and Mg+B fertilization. The yield of milk thistle achenes increased in response to increasing rates of nitrogen fertilization.